Funcionalidade das proteínas EF-Tu e 14-3-3 na virulência de Paracoccidioides brasiliensis - Marcos, Caroline Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis (PCM), a systemic mycosis with broad distribution in Latin America. The adhesion and host cell invasion are critical events involved in the infection and dissemination of the pathogen. Furthermore, they use their surface molecules to bind to extracellular matrix components to establish infection. The successful colonization of host tissues by the fungus is a complex event, usually involving a linker encoded by the pathogen (adhesins) and a cell receptor (often an extracellular matrix component). The identification of adhesion mechanisms, invasion or immune evasion by P. brasiliensis is extremely important and has been investigated in recent studies developed by several groups. In order to study the steps involved from the initial contact of P.brasiliensis until the culminating in its entry into the host cell through the functional characterization of P. brasiliensis membrane proteins, the main targets of interaction with host molecules, is of great importance. The elongation factor Tu (EF-Tu) belongs to the group of proteins called moonlighting such molecules have the ability to perform more than one function, and typically are located in different compartments of the cell. There are reports that EF-Tu of pathogens can act as a virulence factor. This protein has been previously identified in P. brasiliensis by proteomic analysis, but this has not yet been characterized as being interesting then the elucidation of its role in interacting of the fungus with epithelial cells. For this purpose the aim of this study was to produce the recombinant protein and its respective polyclonal antibody, verify your role in the fungus interaction with pneumocytes, extracellular matrix and plasminogen. Also in order to characterize the EF-Tu protein the present study aimed to obtain isolated with low expression of the gene encoding EF-Tu and with this verifies the role of EF-...

Paracoccidioides brasiliensis é o agente causador da paracoccidioidomicose (PCM), micose sistêmica com ampla distribuição na América Latina. A adesão e invasão de células do hospedeiro são eventos cruciais envolvidos na infecção e disseminação do patógeno. Além disso, estes utilizam suas moléculas de superfície para se ligar aos componentes da matriz extracelular para estabelecer a infecção. O sucesso de colonização dos tecidos do hospedeiro pelo fungo é um evento complexo, geralmente envolvendo um ligante codificado pelo patógeno (adesinas) e um receptor da célula (freqüentemente um componente da matriz extracelular). A identificação de mecanismos de adesão, invasão ou evasão imune por Paracoccidioides é extremamente relevante e tem sido alvo de pesquisas recentes desenvolvidas por vários grupos. Neste intuito o estudo dos passos envolvidos desde o contato inicial de P. brasiliensis até os que culminam com a sua entrada na célula através da caracterização funcional de proteínas de membrana de P. brasiliensis, principais alvos de interação com moléculas do hospedeiro, é de grande importância. O Fator de elongação Tu, pertence ao grupo de proteínas denominadas moonlighting, tais moléculas possuem a capacidade de exercer mais de uma função e, normalmente, localizam-se em diferentes compartimentos da célula. Há relatos que EF-Tu de agentes patogênicos possa atuar como um fator de virulência. Previamente esta proteína foi identificada em P. brasiliensis por análise proteômica, sendo diferencialmente expressa quanto o fungo foi cultivado na presença de sangue de carneiro, porém esta ainda não foi caracterizada sendo interessante então a elucidação do seu papel na interação deste fungo às células epiteliais. O objetivo deste estudo foi produzir a proteína EF-Tu recombinante e seu respectivo anticorpo policlonal, verificar...
Keywords: Paracoccidioides brasiliensis; Paracoccidioidomicose; Micologia; Fungos; Virulencia (Microbiologia); Paracoccidioidomycosis